A systematic review and meta-analysis of the association between galectin-3 levels and clinical outcomes in COVID-19 patients - Kacper DZIEDZIC; Kavita BATRA; Michal PRUC; Monika TOMASZEWSKA; Krzysztof KUREK; Murat YILDIRIM; Mahmood BAHRAMIZADEH; Francesco CHIRICO; Nicola Luigi BRAGAZZI; Hicham KHABBACHE; Aldo SITIBONDO; Lukasz SZARPAK; et al. (Journal of Health and Social Sciences)
Introduction: Galectin-3 is a β-galactoside-binding lectin with several roles in the immune- inflammatory response. The aim of this systematic review and meta-analysis was to explain the prognostic value of Galectin-3 on COVID-19 severity and mortality from the existing literature. Methods: PubMed/MEDLINE, EMBASE, SCOPUS, and the Cochrane Central Register of Controlled Trials (CENTRAL) databases were surveyed up to November 10, 2023, for studies reporting data on Galectin-3 levels and the severity and mortality of patients with COVID-19. We performed frequentist random-effects network meta-analysis and presented the standard mean difference (SMD) and 95% confidence interval (CI). Results: Galectin-3 levels among patients with and without COVID-19 varied with the following values: 15.73±13.03 vs. 8.72±5.82 pg/mL, respectively (SMD = 2.59; 95%CI: 1.52 to 3.67; p<0.001). Galectin-3 levels were also statistically different between COVID-19 patients who were severe and those who were not (18.83±15.5 pg/mL vs. 12.43±10.29 pg/mL; SMD = 2.64; 95%CI: 1.45 to 3.83; p<0.001), as well as between COVID-19 patients who survived and those who died (6.24±6.74 pg/mL vs. 13.72±15.92 pg/mL; SMD = -1.79; 95%CI: -2.78 to -0.80; p<0.001). Discussion: Galectin-3 seems to be a useful predictive biomarker of COVID-19 outcomes and needs further evaluation.